Cryopreservation of Stromal Vascular Fraction Cells Reduces Their Counts but Not Their Stem Cell Potency. Issue 7 (July 2019) - Solodeev, Inna; Orgil, Matan; Bordeynik-Cohen, Mor; Meilik, Benjamin; Manheim, Sharon; Volovitz, Ilan; Sela, Meirav; Inbal, Amir; Gur, Eyal; Shani, Nir
Abstract : Background: Adipose-derived stem cells are derived from the nonfat component of adipose tissue termed the stromal vascular fraction (SVF). The use of freshly isolated autologous SVF cells as an alternative to adult stem cells is becoming more common. Repeated SVF administration for improved clinical outcomes is complicated by the need for repeated liposuction. This can be overcome by cryopreservation of SVF cells. The current study aimed to assess whether SVF cells retain their stem cell potency during cryopreservation. Methods: SVF cells isolated from lipoaspirates (donor age: 46.1 ± 11.7 y; body mass index: 29.3 ± 4.8 kg/m 2 ) were analyzed either immediately after isolation or following cryopreservation at −196°C. Analyses included assessment of nucleated cell counts by methylene blue staining, colony-forming unit fibroblast counts, surface marker expression using a flow cytometric panel (CD45, CD34, CD31, CD73, CD29, and CD105), expansion in culture, and differentiation to fat and bone. Results: While cryopreservation reduced the number of viable SVF cells, stem cell potency was preserved, as demonstrated by no significant difference in the proliferation, surface marker expression in culture, bone and fat differentiation capacity, and the number of colony-forming unit fibroblasts in culture, in cryopreserved versus fresh SVF cells. Importantly, reduced cell counts of cryopreserved cells were due, mainly, to a reduction in hematopoietic CD45+ cells, which was accompanied by increased proportions of CD45−CD34+CD31− stem cell progenitor cells compared to fresh SVF cells. Conclusions: Cryopreservation of SVF cells did not affect their in vitro stem cell potency and may therefore enable repeated SVF cell administrations, without the need for repeated liposuction.